Wybrane pojęcia matematyczne i ich interpretacje w ekonomii - Mastalerz-Kodzis, Adrianna; Pośpiech, Ewa (Selected Mathematical Tools and Their Hypothetical Applications, 2006)
Mathematical tools find numerous applications in differing disciplines. The purpose of the article is to present selected mathematical concepts and their applications in economics as well as other disciplines. These concepts are illustrated with examples.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 122-130